Estranged Mother: José Martí, the Matrixial Father in Exile - Skillen, Sarah (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2020)
This article questions the paternal logic of José Martí’s nationalism, through the works Abdala (1869) and Ismaelillo (1882). Martí’s nineteenth-century writing announces the creation of a Cuban nation defined by many in terms of his literary production. However, there remains another Martí, a maternal Martí that escapes our intentions to define and concretize his Work. Beginning with Bracha Ettinger’s concept of the “matrixial,” I maintain that these texts disintegrate the borders between the national body, the individual, and the writer and that this paternal Martí gives way to a maternal relation.